2019
DOI: 10.3390/ijms20164037
|View full text |Cite
|
Sign up to set email alerts
|

Consistent Biomarkers and Related Pathogenesis Underlying Asthma Revealed by Systems Biology Approach

Abstract: Asthma is a common chronic airway disease worldwide. Due to its clinical and genetic heterogeneity, the cellular and molecular processes in asthma are highly complex and relatively unknown. To discover novel biomarkers and the molecular mechanisms underlying asthma, several studies have been conducted by focusing on gene expression patterns in epithelium through microarray analysis. However, few robust specific biomarkers were identified and some inconsistent results were observed. Therefore, it is imperative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 84 publications
3
23
0
Order By: Relevance
“…Lactoferrin or lactotransferrin (LTF) serves as an anti-inflammatory factor and an immunomodulator. LTF which is an iron-binding glycoprotein has been shown upregulated during asthma development in our study as also reported by other studies 26 , 27 . A report by Lourdes Fernández-Delgado et al .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Lactoferrin or lactotransferrin (LTF) serves as an anti-inflammatory factor and an immunomodulator. LTF which is an iron-binding glycoprotein has been shown upregulated during asthma development in our study as also reported by other studies 26 , 27 . A report by Lourdes Fernández-Delgado et al .…”
Section: Discussionsupporting
confidence: 91%
“…Lactoferrin or lactotransferrin (LTF) serves as an anti-inflammatory factor and an immunomodulator. LTF which is an iron-binding glycoprotein has been shown upregulated during asthma development in our study as also reported by other studies 26,27 . A report by Lourdes Fernández-Delgado et al suggested a new mechanism of LTF release by human neutrophils on activation by galectin-3 and claimed the pro-inflammatory role of LTF in allergic asthma 28 .…”
Section: Discussionsupporting
confidence: 91%
“…To determine the changed tendency of pathways in tumors, the Z-score was calculated in each term using the following formula:19,20…”
Section: Methodsmentioning
confidence: 99%
“…Mounting evidence shows that metabolic syndrome and insulin resistance are associated with worsened outcomes of chronic lung disease [ 91 ], as well as microbiome dysbiosis notably in the airways of patients with asthma [ 92 ]. Boldine is predicted to be potential drug for asthma treatment [ 93 ]. Nuciferine can induce relaxation in contracted tracheal rings.…”
Section: Potential Effect On Other Disordersmentioning
confidence: 99%